Exploring geographic information systems - Chrisman, Nicholas R. (New York : John Wiley and Sons, 1997)
This book is divided into three parts: Building blocks of geographic information; Transformations and operations; and The broader context.
Keywords: Geographic information systems; Geographic information systems